Sensing using a fluorescent product generated from Cu2+ assisted L‐Ascorbic acid oxidation. Issue 3 (19th August 2021) - Shen, Qiming; Shu, Tong; Wang, Hui; Fang, Changhao; Zhang, Yingnan; Meldrum, Alkiviathes; Serpe, Michael J.
Abstract: L‐ascorbic acid (AA) is an essential nutrient that plays a vital role in our day‐to‐day body function, and maintaining our health, for example, by serving as an antioxidant. AA oxidation generates various products, some of which have not been identified. In this investigation, we show that the room temperature reaction of AA with copper sulfate (CuSO4 ) generates a product that exhibits blue fluorescence. We studied how various reaction parameters impacted the fluorescence emission intensity, for example, varying the reactant concentration, reaction time, and pH. Mass spectrometry allowed the identification of probable products with the molecular formulae C10 H6 O7 and C10 H8 O8 ; the chemical structures for the possible products are also proposed. Finally, we showed that the fluorescent product can be used for detecting oxygen, Fe, and solution pH. Abstract : We demonstrate that the room temperature reaction of L‐ascorbic acid (AA) with copper sulfate (CuSO4 ) generates a product that exhibits blue fluorescence. The synthetic conditions were optimized to yield maximal fluorescence intensity, and possible fluorescent products proposed ussing mass spectrometric analysis. Finally, we showed that the fluorescent product could be used for detecting O2, Fe 3+, and solution pH.